Investigation on Seed-Filling Effect of Quantitative Precision Filling High-Speed Seed-Metering Device for Maize - Jianxin Dong; Jingtao Wu; Yu Zhu; Xiaojun Gao (Agriculture)
Aiming at the unstable filling effect under high-speed operating conditions of the maize mechanical precision metering device, which easily causes the problem of leakage and multiple filling, a novel filling method was proposed to limit the number of seeds accumulation in front of the filling port by a composite seeding tray and improve the filling effect for single-seed. Meanwhile, a quantitative precision filling seed-metering device for maize was presented. The structural parameter design of the key components was completed, and the principle of improving the seed-filling effect was analyzed and elucidated. The optimal type of grooved teeth for the composite seeding tray was selected, and a Box–Behnken orthogonal optimization experiment was conducted using EDEM simulation. The high-speed seed-metering performance optimization results were validated through a platformed performance experiment. The results indicated that the seed-metering device had higher seed supply capacity, better seed-filling effect, and superior seed-metering performance under the type A grooved teeth condition. When the opening height of the seed barrier was 19.4 mm, the depth of the grooved teeth was 1.2 mm, and the operating speed was 10.7 km·h−1, the seed-metering performance was optimal. The passing, repetitive, and miss rates were 95.1%, 1.6%, and 3.3%, respectively. When the operating speed was 8–14 km·h−1, the passing rate of the seed-metering device was higher than 94.1%, the repetitive rate was lower than 2.3%, and the miss rate was lower than 3.7%. This work provides a reference for enhancing the seed-filling effect of mechanical precision metering devices under high-speed operating conditions.